A High‐Energy Long‐Cycling Solid‐State Lithium‐Metal Battery Operating at High Temperatures. Issue 38 (24th August 2022) - Wang, Sheng; Xu, Ke; Song, Hucheng; Zhu, Ting; Yu, Zhiqian; Song, Xiaopan; Li, Dongke; Yu, Linwei; Xu, Jun; Chen, Kunji
Abstract: High‐energy rechargeable lithium‐ion batteries, especially solid‐state lithium metal batteries, are increasingly required to operate at elevated temperatures in addition to pursuing operation at low temperatures. However, the notorious chemical and electrochemical reactions at the interface between the Li‐anode and solid state electrolyte (SSE) make these batteries lose almost all of their capacity and power at elevated temperatures. Here, a safe and long‐cycle‐life solid‐state Li–CO2 battery operating at elevated temperatures by constructing a stable and high ionic conductive molten salts interface (MSI) is reported. The MSI can effectively improve the interface contact and suppress interface reactions and the thermal runaway between Li‐anode and Li1.5 Al0.5 Ge1.5 P3 O12 (LAGP)‐electrolyte even at high temperatures, thus enabling an ultra‐low interface impedance (≈15 Ω) and discharge/charge overpotential (≈15 mV) for high temperature symmetric battery. In addition, the MSI‐coated LAGP‐electrolyte shows an ultra‐flat and continuous surface that enables a homogeneous Li tripping/plating during cycles. As a result, the Li symmetric battery shows superior cycling stability over 600 h at 0.1 mA cm −2 at 150 °C. The assembled solid‐state Li–CO2 battery using Ru catalysts shows outstanding cycle stability over 980 cycles at 150 °C, with a capacity limitation of 500 mAhg –1 at 500 mA g −1 . Abstract : A long‐cycle‐life solid‐state Li–CO2 battery operating at elevated temperatures by constructing a stable and high ionic conductive molten salts interface (MSI) is reported. The MSI can effectively improve the interface contact and suppress interface reactions between the Li‐anode and LAGP‐electrolyte even at 150 °C, thus the assembled solid‐state Li–CO2 battery shows outstanding cycle stability over 980 cycles.